Bosnia and Herzegovina : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews economic developments in Bosnia and Herzegovina during 1990-95. It describes the monetary arrangements that have evolved in the Federation and Republika Srpska, and summarizes the financial developments. The paper provides an overview of balance-of-payments developments and the external financing requirements associated with the authorities' priority reconstruction program. It describes the exchange rate and trade systems of the two Entities. An assessment of macroeconomic statistics in Bosnia and Herzegovina and a summary of IMF technical assistance activities are also provided.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet